The drifter [large type] - Petrie, Nicholas (Petrie, Nicholas. Peter Ash novel., 2016)
An explosive thriller debut introducing Peter Ash, a veteran who finds that the demons of war aren't easily left behind. After a year spent roaming in nature, Ash returns to civilization to help the widow of a Marine who committed suicide and finds much more than he bargained for.